Three‐Phase Reconstruction Reveals How the Microscopic Structure of the Carbon‐Binder Domain Affects Ion Transport in Lithium‐Ion Batteries. Issue 8 (5th May 2021) - Kroll, Moritz; Karstens, Sarah L.; Cronau, Marvin; Höltzel, Alexandra; Schlabach, Sabine; Nobel, Nikita; Redenbach, Claudia; Roling, Bernhard; Tallarek, Ulrich
Abstract: The morphology of the electrolyte‐filled pore space in lithium‐ion batteries is determined by the solid microstructure formed by μm‐sized active material particles and the smaller‐featured carbon binder domain (CBD). Tomographic reconstructions have largely neglected the CBD, resulting in inadequately defined pore space morphologies at odds with experimental ionic tortuosity values. We present a three‐phase reconstruction of a LiCoO2 composite cathode by focused ion‐beam scanning electron microscopy tomography. Morphological analysis proves that the reconstruction, which combines an unprecedented volume (20 μm minimum edge length) with the hitherto highest resolution (13.9×13.9×20 nm 3 voxel size), represents the cathode's pore space morphology. Pore‐scale diffusion simulations show consideration of the resolved CBD as indispensable to reproduce ionic tortuosity values from electrochemical impedance spectroscopy. Our results reveal the CBD as a convoluted network that dominates the pore space morphology and limits Li + transport through tortuous and constricted diffusion pathways. Abstract : Limiting domain : The multiscale, multiphase reconstruction of a lithium‐ion battery cathode resolves the convoluted pore space within the carbon binder domain (CBD). Morphological analysis and pore‐scale diffusion simulations identify the CBD as the limiting factor for Li + transport in the liquid electrolyte. The CBD microstructure must be explicitly considered to recover the electrochemically determined ionic tortuosity values of porous electrodes.